Study of proposed activities in development of BUMD for regional development - Yurianto Yurianto (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2021)
There are still very few regulations governing the development of BUMD, even though the role of BUMD in regional development is very central. The role of BUMD is very strategic in the regional economy and development. One of these studies focuses on describing the function of BUMD in regional development. While the analytical methods used are APKL, USG, and Mc. Namara methods. In this study, the strategic issue in fostering the selected BUMDs is the lack of comprehensive governance of Regional Equity Participation (PMD) in BUMDs. Of the selected strategic issues, the solution is the preparation of Regional Regulations related to PMD governance. On this basis, five activities are proposed to support the realization of governance of regional capital participation, including the preparation of an academic draft study of regional regulations on the governance of regional equity participation in BUMD. From the results of the analysis, it is suggested that considering that BUMD belongs to the regional government and contains a high dose of politics, the PMD process requires a political approach in addition to a systematic technocratic approach.